Noninvasive prenatal diagnosis (NIPD) of non-syndromic hearing loss (NSHL) for singleton and twin pregnancies in the first trimester - Huanyun Li; Shaojun Li; Zhenhua Zhao; Lingrong Kong; Xinyu Fu; Jingqi Zhu; Jun Feng; Weiqin Tang; Di Wu; Xiangdong Kong (Orphanet Journal of Rare Diseases)
Abstract Background Noninvasive prenatal diagnosis (NIPD) has been proven feasible for non-syndromic hearing loss (NSHL) in singleton pregnancies. However, previous research is limited to the second trimester and the application in twin pregnancies is blank. Here we provide a novel algorithmic approach to assess singleton and twin pregnancies in the first trimester. Methods A 324.614 kb capture panel was designed to selectively enrich target regions. Parental haplotypes were constructed by target sequencing of blood samples from the parents and the proband. Then single nucleotide polymorphisms (SNP) within target regions were classified into four and six categories in singleton and twin pregnancy, respectively. Combining relative haplotype dosage change (RHDO) and the Bayes factor (BF), fetal fraction (FF) and fetal genotype were deduced in singleton and twin pregnancies. The pregnant women’s NIPD results were validated by invasive prenatal diagnosis and Sanger sequencing. Results Sixteen women with singleton pregnancies and one woman with a twin pregnancy were recruited. Among the 16 singleton pregnancies, NIPD was successfully applied in 15 families and the coincidence rate with invasive prenatal diagnosis was 100% (15/15). Only one family NIPD result is “no call” because the imbalance distribution of SNP sites makes it difficult to estimate recombination events. Most (13/15) of pregnant women were diagnosed in the first trimester and the earliest gestation week was the 7th week. The twin pregnancy was a dichorionic diamniotic twin (DCDA). NIPD confirmed one fetus is affected, and another is a carrier with c.299_300delAT of GJB2 gene. Conclusion This study represents the pioneering evidence in the field, demonstrating the feasibility of NIPD for NSHL in twin pregnancies. Moreover, it provides a novel and advanced diagnostic approach for families at high risk of NSHL during pregnancy, offering earlier detection, enhanced safety, and improved accuracy.